ChemInform Abstract: Palladium‐Catalyzed Allylic Cross‐Coupling Reactions of Primary and Secondary Homoallylic Electrophiles. Issue 1 (3rd January 2013) - Stokes, Benjamin J.; Opra, Susanne M.; Sigman, Matthew S.
Abstract A general, simple, and mild title reaction is developed for a broad scope of substrates by using an easily prepared and air stable precatalyst.